Policy Review: Creative Ireland - Rush, Kayla (Irish Journal of Arts Management and Cultural Policy, 2019)
A reflective and critical review of Creative Ireland Programme/Clár Éire Ildánach 2017- 2022, analysed alongside the Creative Ireland Programme 2017 End of Year Report 2018 might seem a bit too late to review Creative Ireland Programme/Clár Éire Ildánach 2017- 2022, given that the ambitious strategy, was first announced in December 2016 and has thus already been in place for over a year, at the time of writing this review. (1) However, reviewing the strategy now provides a unique opportunity to reflect not only on the policy document itself, but also on its early-stage implementation, and the ways in which its first year has been reported and evaluated by those tasked with its success. In this review, I focus on the original strategy document (Creative Ireland), critiqued and analysed in conversation with the 2017 evaluation report (The Creative Ireland Programme/Clár Éire Ildánach End of Year Report 2017; hereafter ‘EYR 2017’ in citations, to differentiate the annual report from the key strategy document)